Highly Sensitive Hydrogen Semiconductor Gas Sensor Operating at Room Temperature. (2015) - Krško, O.; Plecenik, T.; Moško, M.; Haidry, A.A.; Ďurina, P.; Truchlý, M.; Grančič, B.; Gregor, M.; Roch, T.; Satrapinskyy, L.; Mošková, A.; Mikula, M.; et al.
Abstract: Highly sensitive hydrogen semiconductor gas sensor operating at room temperature is presented. The sensor is formed by crossed platinum electrodes in a form of long narrow bridges, separated by a TiO2 thin film (sandwich-like structure). Sensitivity as well as response and recovery time of such sensor strongly depends on the width of the upper electrode. When the width of the upper electrode w is decreased below ∼200 nm, the resistance response (RAir/RH2) of the sensor to 10000 ppm (parts per million) H2 in synthetic air can be as high as ∼10 7 at room temperature, with response time of several seconds. Such steep increase of the sensor response was attributed to the abrupt change of the type of charge carrier transport from thermionic emission to electron drift. Since the resistance of the sensing structures at 0 ppm H2 was over our measurement limit of ∼10 11 Ω, which was limiting the sensor response for low (< 1000 ppm) H2 concentrations, sensor with the top electrode consisting of 500 parallel stripes was prepared. Response of this sensor to 300 ppm H2 at room temperature was more than 10 2 .